Case Report and Literature Review: Bacterial Meningoencephalitis or Not? Naegleria fowleri Related Primary Amoebic Meningoencephalitis in China - Zhou, Wenjuan; Ouyang, Yuzhen; Zhang, Di; Liao, Sheng; Liang, Hui; Zhao, Lingling; Chen, Chunyuan (Frontiers in Pediatrics, 2022)
In China, a 9-year-old boy was transferred to the hospital with fever, vomiting, and headache. The disease rapidly deteriorated into vague consciousness. Applying conventional clinical examinations such as blood and cerebrospinal fluid (CSF) tests, the diagnosis of bacterial meningoencephalitis was firstly drawn, and expectant treatments were adopted immediately. However, the symptoms didn’t alleviate, adversely, this boy died three days after admission. Considering the skeptical points of the duration, such as the unknown infectious bacteria and the pathogen invasion path, blood and CSF samples were then sent for metagenomic next-generation sequencing (mNGS) to ascertain the cause of death. 42899 and 1337 specific sequences of N. fowleri were detected by mNGS in the CSF sample and the blood sample, respectively. PCR results and pathological smear subsequently confirmed the mNGS detection. The patient was finally diagnosed as primary amoebic meningoencephalitis. Besides, in this article, 15 similar child infection cases in the past 10 years were summarized and analyzed to promote the early diagnosis of this rare disease.